State Of The Art In Digital Paleography - Arbain, Nur Atikah; Azmi, Mohd Sanusi; Muda, Azah Kamilah; Abdul Aziz, Maslita; A. Jalil, Intan Ermahani (World Academy Of Research In Science And Engineering (WARSE), 2019)
Digital paleography is an approach used to assist paleographers in deciding the origin of manuscripts. This is done by recording types of writings present in old manuscripts. It uses digital representation of book hands as a tool to support paleographical analyses by, human experts. There are six types of manuscripts selected which are Arabic, Chinese, Jawi, Indian, Latin and Roman. These types of manuscripts are discussed through their current contribution in the digital paleography field. The main purpose of this paper is to discuss the current work on digital paleography for selected types of manuscripts. Thus, we identified the approaches and methods used to define the types of handwritings in old manuscripts